Investing in the Next Generation: The Long-Run Impacts of a Liquidity Shock - Agte, Patrick; Bernhardt, Arielle; Field, Erica; Pande, Rohini; Rigol, Natalia (American Economic Review, 2024)
Poor entrepreneurs must frequently choose between business investment and children's education. To examine this trade-off, we exploit experimental variation in short-run microenterprise growth among a sample of Indian households and track children's education and business outcomes over eleven years. Treated households, who experience higher initial microenterprise growth, invest more in education and are one-third more likely to send children to college. However, only literate households experience child schooling gains and their enterprises stagnate in the long-run. In contrast, illiterate treatment households experience long-run business gains but declines in children's education. Our findings suggest that microenterprise growth has the potential to reduce relative intergenerational educational mobility.